Evaluation of Amplification Targets for the Specific Detection of Bordetella pertussis Using Real-Time Polymerase Chain Reaction - Mohammad Rubayet Hasan; Rusung Tan; Ghada N Al-Rawahi; Eva Thomas; Peter Tilley (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND: Bordetella pertussis infections continue to be a major public health challenge in Canada. Polymerase chain reaction (PCR) assays to detect B pertussis are typically based on the multicopy insertion sequence IS481, which offers high sensitivity but lacks species specificity.